Pelatihan Penyusunan Laporan Keuangan pada Pegawai Koperasi Agro Tamang Makmur - Nopiani Indah; Febriana Louw; Lauw Sun Hiong; Octavian Hartono (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Koperasi Agro Tamang Makmur is a producer cooperative which its main business is to produce goods or services by selling and buying with needs materials so that the prices of the materials and goods produced are lower. In running cooperative business, of course the administrators must be able to arrange the financial statement and report back to their members. Financial reporting is all processes related to the providing of financial information. The preparation of financial statement play an important role, among other things, for internal parties they can be used as a reference in making long-term decisions, and can analyze their performance. The purpose of this PKM activity is to provide training in the preparation of financial statement at Koperasi Agro Tamang Makmur. The assistance provided is in the form of giving basic accounting modules, preparation of financial statement and assistance in the analysis of financial statements that have been prepared. The results of this activity show a significant change from the answers before the training and after the training. The questions answered by the participants after the training were almost all correct. Before the test, there were only 50% of the answers that were answered correctly, after being given training, the correct answers increased to 85%.